Analisis Break Even Point Dalam Kaitan Dengan Pendapatan Spead Boad Kota Jawa - Rohma Kotala; Tri Retno Hariyati; Vury L.A. Sadubun (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2015)
Speadboad businesses that serve sea transport path Mardika Java-City is one source of income for people living in the area were used to serve the communityin order to support their daily activities. Planning on profits from these efforts need to be done as well as possible so that employers speadboad not experience losses due to operational costs are quite high.             The analysis is using the break even point analysis that aimed to quantify the level of production that proceeds equal to the sum of all variable costs and fixed costs.            The result showed that the rste of break even point wiil occur at speadboad entrepreneurs who use premium in the amount of 454 people with a minimum income level of US$1.634 million, then at speadboad which uses kerosene in the amount of 488 people with a minimum income level of US $ 1.7367 million.